Influence of elevated temperature exposure on the residual compressive strength and radiation shielding efficiency of ordinary concrete incorporating granodiorite and ceramic powders - Alaa A. Mahmoud; Alaa A. El-Sayed; Ayman M. Aboraya; Islam N. Fathy; Mohamed A. Abouelnour; Maged E. Elfakharany; Mohy S. Fattouh; Abdelmoniem E. Alahmer; Islam M. Nabil (Scientific Reports)
Abstract This research investigates the potential of utilizing types of construction waste as partial cement replacements within concrete formulations. Notably, granodiorite and ceramic powders were introduced at varying substitution ratios. The impact of these waste materials on the compressive strength and radiation shielding effectiveness of traditional concrete was evaluated under both ambient and elevated temperature conditions. Additionally, several microstructural tests like X-ray diffraction (XRD), Thermogravimetric analysis (TGA), and Energy dispersive X-ray (EDX) were conducted to assess the influence of using the optimal replacement ratios of the investigated waste powders on the studied properties of concrete. Results revealed a substantial improvement in the investigated properties of the concrete. Remarkably, a 7% substitution with waste granodiorite powder (WGDP) yielded the optimal mix for compressive strength, exhibiting increases of 24.7%, 26.1%, 22%, and 28% at room temperature, 400 °C, 600 °C, and 800 °C, respectively. Likewise, a 7% replacement with waste ceramic powder (WCP) exhibited quantifiable improvements in compressive strength, with approximately 23.1%, 23.5%, 25.6%, and 32.6% at room temperature, 400 °C, 600 °C, and 800 °C, respectively. For microstructure analysis, XRD analysis confirmed enhanced pozzolanic activity with reduced portlandite and increased calcium silicate hydrate (CSH) formation for the optimal WGDP and WCP mixes compared to the control mix. TGA analysis revealed higher CSH decomposition in modified mixes, indicating greater pozzolanic reaction. Furthermore, density and EDX analyses showed denser microstructures in waste powders-incorporated mixes due to finer particle packing and secondary hydration effect. The radiation shielding investigation show that the optimum WCP mix (C7) enhances the attenuation capability of concrete. The optimum WGP mix (GD7) also contributes positively to attenuation, though to a lesser extent than C7. Ordinary concrete (CO) exhibits the lowest $$\it \:\text{C}\text{M}$$ LAC, indicating its baseline performance in linear attenuation. Thus, the studied CM-concrete samples provide the best protection against fast neutrons which pave the way for the utilization of industrial waste, especially ceramic and granodiorite waste, in enhancing the properties of concrete towards radiation shielding against gamma rays and neutrons.